KETIDAKLANGSUNGAN EKSPRESI DALAM PUISI JARAK MAGRIB KARYA MUAMMAR QADAFI MUHAJIR KAJIAN SEMIOTIKA RIFFATERRE - Wa Ode Kartinasari; Lilik Rita Lindayani; Nurlailatul Qadriani (Program Studi Sastra Indonesia Fakultas Ilmu Budaya Universitas Halu Oleo, 2023)
The problem that arises in this study is how the indirectness of the expression contained in the poem Distance Magrib by Muammar Qadafi Muhajir in Rifaterre's Semiotics study. The purpose of this study was to analyze the indirectness of expression in the poem Distance Magrib by Muammar Qadafi Muhajir. The theory used in this study is the semiotic theory developed by Michael Riffaterre. This type of research is library research using qualitative descriptive methods. The data in this research are in the form of words, phrases, sentences, lines, and lines that show the indirectness of expression in the poem Distance Maghrib by Muammar Qadafi Muhajir. The results of this study prove that the poetry of Distance Magrib has meaning and is indicated in the form of indirect expression in the form of meaning replacement, namely in the form of metaphorical figure of speech, simile figure of speech, personification figure of speech, and allegory figure of speech. There are deviations in meaning caused by the use of ambiguous sentences, contradictions, and nonsense, as well as the creation of meaning found in rhyme/sound forms, enjambement homologues, and typography that affect the text, so analysis is necessary. Keywords: Indirect Expression, Poetry, Riffaterre Semiotics